Development dynamics in the Philippines historical perspectives: 1950 - 2010 - Florián A. Alburo (University of the Philippines, School of Economics (UPSE), 2015)
This paper attempts to explore the use of an OECD Multi-Dimensional Country Review (MDCR) framework in understanding the long-term development history of the Philippines. The MDCR recognizes the multiplicity of development objectives countries usually pursue and therefore the associated multiplicity of challenges and opportunities. Following a conventional dichotomy of explaining the country's development dynamics into economic and non-economic factors, the paper reviews the historical economic record and examines more recent non-economic hypotheses. While the latter is mostly political explanations it tries to link them to economic outcomes yet it is weak in tracing the mechanisms of the linkage despite using more rigorous methodologies. The paper then proceeds with hypothesizing that the long-term (political) behavior of breaking the country into finer geographical (and political) entities has been inimical to its sustainable long-term (economic) growth. The splitting of provinces, creation of new ones, of legislating more congressional districts, and further break-up of even the lowest government levels clearly fragment markets, raise real financial and transactions costs, bloat government budgets and the bureaucracy, and add burden to the private sector environment. Partial evidence is explored showing this behavior along the country's long-term development history and some policy directions are suggested.
Keywords: O11; O15; O43; J68; 330; Development dynamics in the Philippines; MDCR; Philippines